2020
DOI: 10.5194/wcd-1-577-2020
|View full text |Cite
|
Sign up to set email alerts
|

Vertical cloud structure of warm conveyor belts – a comparison and evaluation of ERA5 reanalysis, CloudSat and CALIPSO data

Abstract: Abstract. Warm conveyor belts (WCBs) are important cyclone-related airstreams that are responsible for most of the cloud and precipitation formation in the extratropics. They can also substantially influence the dynamics of cyclones and the upper-level flow. So far, most of the knowledge about WCBs is based on model data from analyses, reanalyses and forecast data with only a few observational studies available. The aim of this work is to gain a detailed observational perspective on the vertical cloud and prec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 65 publications
1
16
0
Order By: Relevance
“…WCBs are coherent airstreams that originate in the cyclone's warm sector and rapidly move poleward while ascending to the upper troposphere. They form elongated cloud bands with warm clouds in their inflow, mixed-phase clouds at mid-levels, and ice clouds in the upper troposphere (Joos and Wernli, 2012;Wernli et al, 2016;Binder et al, 2020). The intense cloud-diabatic processes within the ascending airstreams modify potential vorticity (PV) in the atmosphere (Wernli and Davies, 1997;Madonna et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…WCBs are coherent airstreams that originate in the cyclone's warm sector and rapidly move poleward while ascending to the upper troposphere. They form elongated cloud bands with warm clouds in their inflow, mixed-phase clouds at mid-levels, and ice clouds in the upper troposphere (Joos and Wernli, 2012;Wernli et al, 2016;Binder et al, 2020). The intense cloud-diabatic processes within the ascending airstreams modify potential vorticity (PV) in the atmosphere (Wernli and Davies, 1997;Madonna et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…WCBs are coherent airstreams that originate in the cyclone's warm sector and rapidly move poleward while ascending to the upper troposphere. They form elongated cloud bands with warm clouds in their inflow, mixed-phase clouds at mid-levels and ice clouds in the upper troposphere (Joos and Wernli, 2012;Wernli et al, 2016;Binder et al, 2020). The intense cloud-diabatic processes within the ascending airstreams modify potential vorticity (PV) in the atmosphere (Wernli and Davies, 1997;Madonna et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The modelling study by Joos and Forbes (2016) showed that the vertical cloud structure of a WCB is affected by seemingly small changes in the implementation of the microphysics, with direct implications for the detailed shape and amplitude of the upper-tropospheric ridge influenced by the WCB outflow. More recently, Binder et al (2020) systematically compared the vertical structure of WCB-related clouds in the latest European Centre for Medium-Range Weather Forecasts (ECMWF) reanalysis dataset, ERA5 (Hersbach et al, 2020), with profiles derived from satellite-based lidar and radar observations and concluded that the model reproduces the overall cloud structure quite well but underestimates ice and snow water content in the mixed-phase layer in WCBs above the melting layer. Such weaknesses in models might arise from various assumptions made in microphysical parameterisations that account for the subgrid-scale nature of the cloud processes and often lead to uncertainties in NWP (Illingworth et al, 2007;Rodwell et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Their sensitivity experiments with the ECMWF forecast model revealed that with the corrected low-level moisture in the initial conditions the WCB outflow would have occurred at a lower potential temperature level and produced a less developed upper-level ridge. The humidity in the WCB inflow, however, is not only determined by boundary layer ventilation (Boutle et al, 2011;Pfahl et al, 2014). It can also be affected by a recycling of moisture within the WCB, which occurs, e.g., when raindrops from an elevated layer of the WCB fall into a sub-saturated lower layer of the WCB inflow where they evaporate (Crezee et al, 2017;Attinger et al, 2019;Spreitzer, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation